DEVELOPMENT OF INTEGRATED EDUCATION IMPLEMENTATION MODEL: INTEGRATION OF ISLAMIC VALUES, PANCASILA, LOCAL WISDOM AS A STRENGTHENER OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Marwan; Siraj; Riandi Marisa (CV. RADJA PUBLIKA, 2024)
The National Education System in Aceh is organized in an Islamic and integrated manner to achieve educational goals. Initial research findings found several factors causing the less than optimal implementation of integrated education in Aceh, including: 1) minimal socialization, communication, and coordination between various stakeholders; 2) schools do not understand the concept of implementing integrated education; 3) there are no technical instructions; and 4) low participation of parents and the community with schools in supporting integrated education. Based on these problems, knowledge and skills are needed from schools in implementing an integrated education system based on Islamic, national and Acehnese values ​​as an educational model in Aceh. The concept of an integrated education model was then developed into an educational model that can be used by all schools in Aceh. In order for these problems to be overcome, a priority scale is needed in building and making changes in various aspects as part of educational reform, namely in the regulatory, professional aspects; and management aspects. The purpose of the research in the first year was to identify the potential and implementation of the implementation of integrated education in Aceh and the form of efforts by the Aceh Government in maximizing the implementation of integrated education as a reinforcement of the implementation of the independent curriculum using a SWOT analysis. This study uses a Mix Method approach using a descriptive method. The research stages were carried out by following The Exploratory Sequential Design. There is a sequence in the research stages, starting from qualitative research and continuing with quantitative. The priority of qualitative data collection and analysis was carried out in the early stages (first year). Building on the results of the exploratory analysis in the first stage, the researcher continued the next stage with a quantitative method to test or generalize based on initial findings. The researcher then interpreted how the results of qualitative research were built by initial findings (qualitative data). The results of the study have produced recommendations for a more objective and applicable integrated education implementation model as input in the framework of formulating education policies. The novelty in the study is a model for implementing education based on Islamic values, Pancasila and local wisdom of Aceh as a reinforcement of the independent curriculum which culminates in the creation of humans who have the strength of NATIONALISM, IPTEKS and IMTAQ in supporting Advanced Indonesia so that it will produce intelligent, healthy, brave and highly competitive human resources in the 4.0 era. The output of this research in the first year was 1 (one) scientific paper in an accredited national journal and 1 (one) article in a reputable international journal and 1 (one) intellectual property rights (IPR) ownership in the form of a research report.